IL-11 and IL-11Rα immunolocalisation at primate implantation sites supports a role for IL-11 in placentation and fetal development - Stoikos C; Martin H; Enders AC; Liu Y-X; Robb L; Dimitriadis E; Wallace E; Salamonsen LA (BMC, 2003)
Abstract Embryo implantation, endometrial stromal cell decidualization and formation of a functional placenta are critical processes in the establishment and maintenance of pregnancy. Interleukin (IL)-11 signalling is essential for adequate decidualization in the mouse uterus and IL-11 promotes decidualization in the human. IL-11 action is mediated via binding to the specific IL-11 receptor α (IL-11Rα). The present study examined immunoreactive IL-11 and IL-11Rα in cycling rhesus monkey endometrium, at implantation sites in cynomolgus and rhesus monkeys and in human first trimester decidua and defined distinct spatial and temporal patterns. In cycling rhesus monkey endometrium, IL-11 and IL-11Rα increased in both basalis and functionalis regions during the secretory compared with the proliferative phase, with changing cellular locations in luminal and glandular epithelium and stroma. The patterns were similar overall to those previously described in human endometrium. Differences were seen in immunostaining during implantation in cynomologus and rhesus monkey. In the cynomolgus, very little staining for IL-11 or IL-11Rα was seen in syncytio- and cyto-trophoblast cells in the villi between days 12 and 150 of pregnancy although there was moderate staining in cytotrophoblast in the shell between days 12 and 17 and in subpopulations of cytotrophoblast cells invading the arteries at day 17. By contrast in the rhesus monkey between days 24 and 35 of pregnancy and in human first trimester placenta, cyto- and syncytio-trophoblast in the villi but not cytotrophoblast in the shell were positively stained. The most intense staining for both IL-11 and IL-11Rα was present within the decidua in the maternal component of implantation sites in all three primates but moderate staining was also present in maternal vascular smooth muscle and glands perivascular cells and epithelial plaques. These results are consistent with a role for IL-11 both during decidualization and placentation in primates.